Shaw Wallace Building - Ghosh, Ayan (2023)
The Shaw Wallace building on Walchand Hirachand Marg is now known as the Bank of Baroda building, which is housed in it. The ground floor has semi-circular arched windows while the windows on the upper levels are rectangular and framed with plaster moldings. Above the central entrance is a pediment supported on decorative brackets which is a balcony with balustrades.